Russian loanwords in Skolt Saami - Juutinen, M. (Markus) (Finnisch-Ugrische Forschungen, 2022)
Abstract The distribution of the Russian loan vocabulary within the Saami languages centers on Skolt, Akkala, Kildin, and Ter Saami. In Skolt Saami, this loanword stratum forms the largest loanword stratum and contains more than 750 lexemes. Despite the significance of the loanword stratum, there has hardly been any actual analysis of the Russian loanwords in the Saami languages. This paper aims to fill this gap by presenting an overview of Russian vocabulary in Skolt Saami from a phonological, morphological, and semantic point of view. Besides analyzing the loanwords, approximately 150 new loan etymologies are discussed and some thirty new comparisons with Russian loanwords proposed in other Saami languages. It turns out that the Russian loan lexicon is relatively recent, and most if not all the words were borrowed from the Northwestern dialects of Russian between the beginning of the 17th century and 1920. Semantically the vocabulary is heterogenous. The most important semantic categories include religion, clothing, buildings and houses, diet, as well as administration and society.